Differentiating process performance of various coagulants in removal of congo red and orange G dyes - Prajapati, Kavita; Sorokhaibam, Laxmi Gayatri; Bhandari, Vinay M.; Killedar, D. J.; Ranade, Vivek V. (International Journal of Chemical Reactor Engineering, 2016)
Two refractory azo dyes-Congo red and Orange G, especially at high concentrations were subjected to coagulation with different conventional coagulants and newer formulations developed from Aluminum sulfate, Iron (III) chloride, Aluminium chloride, Poly diallydimethylammonium chloride (Poly DADMAC) and Poly Aluminium Chloride (PAC). The highest COD reduction of 99 % was obtained with PAC SAB 18 (Powder Grade PAC) for Congo red at pH 4.5 while the color removal of 99 % was achieved with almost all the coagulants in the present study at specific pH within 3-8. The optimum dose for the iron-based coagulant is 200 mg/L while that of aluminum-based coagulants and PAC is 150-200 mg/L. Results showed that Orange G was more difficult to remove with a maximum COD removal of 65 % and 35 % color removal using various formulations. The combinational formulations of inorganic-inorganic and inorganic- organic produced a substantial enhancement in COD and color removal and reduced sludge. PAC-Fe30/70 produces the minimum sludge of 50 mL/g on Congo red. pH in the range 3-9 showed high reductions in COD and color (90-99 %) for Congo red while jerky rise in COD and color reduction was observed in the case of Orange G after pH 9. An attempt to understand the dye coagulation mechanism has been made based on the specific difference in dye structure and cation speciation.
Keywords: coagulation; Congo red; dye removal; Orange G; Wastewater treatment